Detection of KRAS and BRAF mutations in advanced colorectal cancer by allele-specific single-base primer extension. (November 2011) - Balschun, Katharina; Wenke, Ann-Kathrin; Röcken, Christoph; Haag, Jochen
Evaluation of: Magnin S, Viel E, Baraquin A et al. A multiplex SNaPshot assay as a rapid method for detecting KRAS and BRAF mutations in advanced colorectal cancers. J. Mol. Diagn. 13(5), 485–492 (2011). Since mutations in the KRAS and BRAF genes are associated with resistance to therapy with anticancer drugs targeting the EGF receptor pathway, the analysis of KRAS and BRAF mutational status has become an important tool in the clinical management of patients with advanced colorectal cancer. To be useful in the clinical setting, a diagnostic assay has to address several issues related to the sensitivity and specificity of the method, the modularity of the assay, the turnaround time and the running costs. A variety of methods have been applied to the diagnosis of KRAS and BRAF mutational status. Although there is a good concordance between different methods, differences exist regarding sensitivity, multiplexing capacity and costs. In this article, we review a recently published assay for the simultaneous detection of diagnostically relevant KRAS and BRAF mutations and discuss this work in the context of conventional diagnostic methods.